The Psychoanalysis of the Main Character in Handling Conflicts in Chernobyl TV Series - I Gusti Agung Ayu Ningrat Mayura Putri; I Gusti Agung Istri Aryani; Ni Ketut Widhiarcani Matradewi (Humanitatis : Journal of Language and Literature, 2021)
This study is aimed to describe the psychological aspects of the main character in handling the conflict the main character experienced in the story. The data for this study were taken from a TV Series entitled Chernobyl and collected by using observation technique and note taking technique. The collected data then analyzed by using qualitative method. There are two theories applied in this study. The first theory is the theory proposed by Kenney (1966) about conflict that divided into internal conflict and external conflict. The second theory is the theory proposed by Freud (1923) about psychoanalysis that divide human’s psychological aspect into three; id, ego, and superego. The result of the analysis showed that the main character mainly encountered external conflicts because he had many different opinions with other characters. Afterward, the id, ego, and superego are used in handling the conflicts he experienced.